Coroners' investigations of suicide in Australia: The hidden toll of borderline personality disorder. (October 2020) - Broadbear, Jillian H.; Dwyer, Jeremy; Bugeja, Lyndal; Rao, Sathya
Abstract: Borderline Personality Disorder (BPD) is associated with a high risk of death by suicide. Our study describes a population-based analysis of Coroners' investigations of suicides where there was evidence of a BPD diagnosis. We utilised the Victorian Suicide Register to identify suicides occurring between 2009 and 2013 where evidence of a BPD diagnosis was recorded. Of the 2870 suicides during this period, 181 (6.3%) had a BPD diagnosis recorded. Evidence of other diagnosed personality disorders was recorded in an additional 14 (0.5%) suicides and BPD was suspected in another 72 (2.5%) suicides. Information coded in the 181 diagnosed BPD suicides was compared with the 2689 suicides without a BPD diagnosis. Compared to the 'no BPD suicide group', the 'BPD suicide group' was younger, comprised a smaller proportion of women, had greater diagnostic complexity, a higher proportion of death by drug overdose, and a higher proportion of social and contextual stressors. 99% of people with a BPD diagnosis who died from suicide had contact with emergency and mental health services within 12 months of death; 88% sought help from these services within 6 weeks of death. These findings demonstrate the magnitude of this most severe outcome of mental illness, confirming that BPD belongs in the same category as schizophrenia, bipolar disorder and depressive disorder with respect to suicide representation. The help-seeking behaviours evident in almost all cases highlight a critical window of opportunity for providing timely support and treatment to help avert future deaths.